(untitled) (Research, Society and Development, 2023)
Introduction: Thyroid function is closely associated with neuropsychological functions, including mental state and cognitive functions. Subclinical hypothyroidism (HSC) is defined as a condition with elevated levels of thyroid stimulating hormone (TSH) and normal levels of free thyroxine (T4). Objective: to demonstrate the relationship between hypothyroidism and depressive disorder. Methodology: this is a descriptive integrative review type research. The research was carried out through online access in the National Library of Medicine databases (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, EBSCO Information Services, in August 2021. Results: Although the role played by thyroid hormones in the pathophysiology of mental disorders is unclear, it has been suggested that small changes in thyroid hormone levels, even within the normal range, may be related to altered brain function in depression. Currently, there are 2 explanatory hypotheses: the serotonin deficit and the norepinephrine deficit in the central nervous system caused by hormonal disturbances. It is important to emphasize that the thyroid-psychic pathway is bidirectional, therefore, both thyroid alterations can cause depressive symptoms or exacerbate a previous psychiatric pathology, and depression can promote thyroid disorders, this second case being less frequent. Conclusion: The role of thyroid function in depressive illness is unclear. Although there is some evidence that mild thyroid alterations predispose to cases of depression, the specific abnormalities involving the thyroid and depressive conditions remain poorly known. However, there is a causal link.